Does MRI Knee in Those over 50 Years with Knee Pain in Osteoarthritis Alter Management? A Retrospective Review - Murphy, Alexandra N.; Yelverton, Bryan; Clesham, Kevin; Hassell, Kathy; Kavanagh, Eoin; Eustace, Stephen; Cashman, James (The Journal of Knee Surgery, 2021)
Knee osteoarthritis (OA) is a significant cause of pain and disability worldwide. Imaging provides diagnosis, prognostication, and follow-up. Radiographs are first line, useful, and inexpensive. Magnetic resonance imaging (MRI) can detect additional features not seen on radiograph, but it is of questionable usefulness in the management of knee OA. Our aim was to investigate the usefulness of MRI in the workup of knee OA and whether MRI alters management in knee OA. A retrospective review was performed of consecutive MRI knees performed for knee pain in those over 50 years. Clinical information and documentation of management plan pre- and post-MRI were collected. Assessment was made whether the MRI results influenced the final management plan. Of the 222 MRI knees included for study, the majority (62.2%) had not had a recent radiograph. OA was reported in 86.9% of radiographs and 89.6% of MRI. On MRI, the most prevalent finding was tearing/abnormality of the medial meniscus, seen in 47% of MRIs overall, increasing to all in severe OA. MRI assisted with management in 9.5% of all (21/222) patients, and changed management plans in 23% of those that had documented management plans prior to the MRI (6/26 patients). MRIs can guide tailored management in knee OA and are useful for surgical planning; however, they should only be ordered in certain cases, and a radiograph should always be performed first. MRI should be considered if symptoms are not explained by OA alone or the appropriate treatment option requires MRI.
Keywords: MRI; knee; arthroscopy; osteoarthritis